2022
DOI: 10.3390/nano12172916
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization with Polyphenols of a Nano-Textured Ti Surface through a High–Amino Acid Medium: A Chemical–Physical and Biological Characterization

Abstract: The study aimed to identify an effective mechanism of adsorption of polyphenols on a nano-textured Ti surface and to evaluate the osteogenic differentiation on it. The source of polyphenols was a natural extract from red grape pomace. A chemical etching was used to form an oxide layer with a nanoscale texture on Ti; this layer is hydrophilic, but without hydroxyl groups with high acidic–basic chemical reactivity. The samples were characterized by electron and fluorescence microscopies, UV–Vis spectroscopy, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Epifluorescence and SEM imaging show that structurally, the clot consists of a three-dimensional fibrin network embedding variable amounts of platelets, leukocytes, and erythrocytes, distributed inhomogeneously throughout the surface. Although the combination of nanotopography and hydrophilicity (two surface characteristics of Nano-Ti) [ 20 , 21 ] might contribute to pronounced blood coagulation [ 29 ], it has been shown that implant surfaces structured at the micro-scale are more efficient at retaining the fibrin clot, an event that is crucial for bone repair to occur at the tissue–implant interface [ 30 ]. Therefore, considering the only occasional occurrence of microtopographic features on the Nano-Ti surface (not shown) and the inhomogeneity of the blood clot on it, it may be more appropriate to hierarchically structure the Ti surface at the micro- and nanoscale [ 31 ], or to even functionalize it with a molecule that could contribute to the formation of a more homogenous blood clot/fibrin clot in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epifluorescence and SEM imaging show that structurally, the clot consists of a three-dimensional fibrin network embedding variable amounts of platelets, leukocytes, and erythrocytes, distributed inhomogeneously throughout the surface. Although the combination of nanotopography and hydrophilicity (two surface characteristics of Nano-Ti) [ 20 , 21 ] might contribute to pronounced blood coagulation [ 29 ], it has been shown that implant surfaces structured at the micro-scale are more efficient at retaining the fibrin clot, an event that is crucial for bone repair to occur at the tissue–implant interface [ 30 ]. Therefore, considering the only occasional occurrence of microtopographic features on the Nano-Ti surface (not shown) and the inhomogeneity of the blood clot on it, it may be more appropriate to hierarchically structure the Ti surface at the micro- and nanoscale [ 31 ], or to even functionalize it with a molecule that could contribute to the formation of a more homogenous blood clot/fibrin clot in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain Nano-Ti, commercially pure grade 2 Ti discs (Realum, São Paulo, Brazil), modified to exhibit a hollowed surface ( Figure S1 ), were cleaned by sonication and etched in a solution consisting of equal volumes of concentrated 30% H 2 O 2 and H 2 SO 4 (95–97%) for 4 h (10 mL/disc) at room temperature (RT) [ 12 , 20 ]. Then, they were rinsed in distilled water, air dried, and autoclaved.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The here-reported surface modification is a functionalization that produces the grafting of a thin (molecular) layer of TA without any modification of the surface roughness and morphology, as previously observed by the authors on different titanium substrates. 31,32 3.3. Compositional and Chemical State Analysis.…”
Section: Surface Characterizationmentioning
confidence: 99%
“…Chemisorption allows a controlled and pH-dependent release that is beneficial for targeted effects. 31 In the present study, we used tannic acid polyphenols from a natural extract for functionalization, as they possess multifunctional properties, 32 for example, antibacterial, anti-inflammatory, antitumor, antiviral, and cytocompatible characterizations that were proved thanks to the presence of high amounts of phenolic compounds and pyrogallol groups. 33 Therefore, there has been increased interest in the implementation of tannic acid to chemically modify the surface of materials in terms of their application as implant biomaterials.…”
Section: Introductionmentioning
confidence: 99%